COMPLIANCE OF THE LEGAL TREATMENT OF EXPERIMENTAL ANIMALS IN SERBIAN LEGISLATION WITH THE LEGISLATION OF THE EUROPEAN UNION - Vidić Trninić, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The author focuses on compliance of the legal treatment of experimental animals in Serbian law with the provisions of the European Convention for the Protection of Vertebrate Animals used for Experimental and other Scientific Purposes, as well as the provisions of the European Union Directive on the protection of animals used for scientific purposes, currently in force. Analysing, on one hand, the treatment that experimental animals have under the law of Europeаn Union, and on the other hand, the treatment that they have in the law of Serbia, in accordance with the relevant acts and subordinate legislation acts, this article seeks to answer the question whether the degree of legal protection of experimental animals in domestic law is satisfactory, as well as whether and to what extent the relevant national legislation complies with the European standards. At the same time, the article attempts to point out the appropriate measures necessary to be taken in the future in order to achieve as high quality and comprehensive protection of experimental animals as possible in Serbian law.